The sociology of religious movements - Bainbridge, William Sims (Routledge, 1997)
Explaining how religion and society transform each other, this book explores such movements as Holiness, Adventism, religious communes, Satanism, New Age and democratization. The Sociology of Religious Movements is the culmination of work begun in The Future of Religion (the 1986 award winner of the Society for the Scientific Study of Religion) and A Theory of Religion (1993 award winner of the Pacific Sociological Association). Explaining religious schism, innovation, and conversion to show how religion and society transform each other, this book explores such movements as: Holiness, Adventism, religious communes, Children of God, Satanism, New York City Mission Society, New Age, Asian imports, and democratization.